2022
DOI: 10.1051/0004-6361/202243485
|View full text |Cite
|
Sign up to set email alerts
|

The size of monomers of dust aggregates in planet-forming disks

Abstract: Context. The size of the constituent particles (monomers) of dust aggregates is one of the most uncertain parameters directly affecting collisional growth of aggregates in planet-forming disks. Despite its importance, the monomer size has not yet been meaningfully constrained by disk observations. Aims. We attempt to derive the monomer size from optical and near-infrared (IR) polarimetric observations of planet-forming disks. Methods. We performed a comprehensive parameter survey on the degree of linear polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 126 publications
1
28
0
Order By: Relevance
“…In such a scenario, results may be improved by utilizing a more appropriate polarization curve in place of Equation (4). This may be particularly relevant for observations at optical wavelengths, where fractional polarization curves can take more complex "rippled" shapes for some compositions (e.g., for the case of amorphous carbons in Tazaki & Dominik 2022).…”
Section: Considerations and Limitationsmentioning
confidence: 99%
“…In such a scenario, results may be improved by utilizing a more appropriate polarization curve in place of Equation (4). This may be particularly relevant for observations at optical wavelengths, where fractional polarization curves can take more complex "rippled" shapes for some compositions (e.g., for the case of amorphous carbons in Tazaki & Dominik 2022).…”
Section: Considerations and Limitationsmentioning
confidence: 99%
“…Coagulation instability will be inefficient in such a case. However, Tazaki & Dominik (2022) recently suggested that a monomer size is no greater than 0.4 μm based on optical and near-infrared polarimetric observations of several planet-forming disks. We thus expect that the above reference values are valid.…”
Section: On the Critical Fragmentation Velocity And Turbulence Strengthmentioning
confidence: 99%
“…If the monomer size is larger, the critical energy for separating monomers in contact becomes smaller (e.g., Johnson et al 1971;Chokshi et al 1993), which makes the critical velocity smaller (e.g., Dominik & Tielens 1997;Wada et al 2007Wada et al , 2008. According to a recent study by Tazaki & Dominik (2022), optical and near-infrared polarimetric observations suggest that a monomer size is no greater than 0.4 μm. Thus, the critical velocity can be roughly three times lower than the above value (e.g., see Equation (8) in Wada et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4. This may be particularly relevant for observations at optical wavelengths, where fractional polarization curves can take more complex "rippled" shapes for some compositions (e.g., for the case of amorphous carbons in Tazaki & Dominik 2022).…”
Section: Considerations and Limitationsmentioning
confidence: 99%